Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1101/2023.10.16.562607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diurnal fluctuations in steroid hormones tied to variation in intrinsic functional connectivity in a densely sampled male

Hannah Grotzinger,
Laura Pritschet,
Pavel Shapturenka
et al.

Abstract: Most of mammalian physiology is under the control of biological rhythms, including the endocrine system with time-varying hormone secretion. Precision neuroimaging studies provide unique insights into the means through which our endocrine system regulates dynamic properties of the human brain. Recently, we established estrogen's ability to drive widespread patterns of connectivity and enhance the functional efficiency of large-scale brain networks in a woman sampled every 24h across 30 consecutive days, captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Functional coherence in posterior visual networks were particularly sensitive to TOD. Nodes belonging to central and peripheral visual networks demonstrated some of the strongest associations with diurnal variation in testosterone, estradiol, and cortisol (Grotzinger et al, 2023), paralleling the changes in GMV and CT we see here. Hormonal regulation of visual cortex has been demonstrated in rodent studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Functional coherence in posterior visual networks were particularly sensitive to TOD. Nodes belonging to central and peripheral visual networks demonstrated some of the strongest associations with diurnal variation in testosterone, estradiol, and cortisol (Grotzinger et al, 2023), paralleling the changes in GMV and CT we see here. Hormonal regulation of visual cortex has been demonstrated in rodent studies.…”
Section: Discussionsupporting
confidence: 71%
“…The methods for this study are reported in Grotzinger et al, 2023. Briefly, the participant underwent venipuncture and brain imaging every 12-24 hours for 30 consecutive days. At each session the participant completed a questionnaire to assess stress, sleep, and mood states, followed by endocrine sampling at 7 A.M. (morning sessions) and/or at 8 P.M. (evening sessions).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a dense-sampling approach has been applied on a 23-year-old female (28&Me study; [46]) and a 26-year-old male (28&He study; [47]), who were respectively tested for 30 and 20 consecutive days in time-locked study sessions including brain imaging, venipuncture and salivary sampling, and self-report mood questionnaires. These studies -as well as subsequent studies using the female dataset (e.g., [48][49][50][51])-measured day-to-day changes in functional brain activity, reporting associations between hormonal fluctuations and the reorganization of functional networks.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, we capitalize on a dense sampling approach to investigate intraindividual variability along the S-A axis in two healthy young adults, one male and one female, from the aforementioned openly-available datasets [46,47]), probing the sexspecificity of neuroendocrine factors (i.e., steroid hormone levels), as well as perceived stress, associated with daily variability in functional brain organization. We first applied a dimensionality reduction algorithm to daily functional connectivity matrices in order to compute the S-A axis.…”
Section: Introductionmentioning
confidence: 99%